THERMAL EFFECTS OF SECONDARY ELECTROTHERMAL ALLOYING AND REFINING OF STEEL - KharchenkoАlеxander; Lichkonenko, Natalia (Scientific Journal "Metallurgy", 2021)
Analysis of the thermal effects of materials and electricity in the out-of-furnace treatmentof 09G2S and 35HGSA steels using technology of secondary electrothermal alloying and refining(SEAR) has been carried out. The features of the change in the thermal effects of materialsare considered depending on the specific charge of the slag and the portion of added materials.It is shown that, depending on the current state of the "metal-slag-gas" system, the thermal effectsof materials can be either positive and negative, which is due to the complex interaction ofthe elements that make up their composition with liquid steel and slag. Main components ofsuch interaction are listed: absorption of the physical heat of the melt by the material with theambient temperature; imperfection of a multicomponent metal solution; interaction of elementswith oxygen dissolved in liquid metal. It was found that the thermal effects of materials duringthe processing of low-alloy steels using the SEAR technology significantly depend on both theproportion of the introduced materials and the specific charge of the slag. On the basis of thermodynamicanalysis of the "metal-slag-gas" system, formulas for calculating heat effects wereobtained. Thermal effects of all materials used for deoxidationalloying, including ferroalloys, siliconcarbide, lime, and electricity, have been calculated. It is shown that an increase in the specificcharge of the slag reduces the thermal effect of secondary aluminum and other materialswith a large exothermic effect. At the same time, there is a relative increase in the heat effect ofcarbonaceous materials such as silicon carbide. Using steels 09G2S and 35HGSA as an example,an extreme dependence of the melt temperature on the portion of added materials isshown. Generalizing conclusions have been made regarding factors affecting the thermal effectswhen adding materials into liquid steel.